The Role of Food Quality and Halal Certificate to Improve Consumer Satisfaction and Loyalty - Walter Tabelessy (International Journal of Social Service and Research, 2023)
This study aims to analyze the role of food quality and halal certificates in increasing consumer satisfaction and loyalty. This research is a type of survey research using questionnaires as the main data collection tool using the 5 Likert Scale Points. The population in this study is Bidadari's Catering consumers. The sample in this study was determined based on the inverse square root method so that a total of 99 respondents were obtained. The sampling technique used is purposive sampling. The data in this study were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with WarpPLS 8.0 application. The results of the data analysis show that all hypotheses proposed are accepted, namely food quality plays a positive role in increasing consumer satisfaction, food quality plays a positive role in increasing consumer loyalty, halal certificates play a positive role in increasing consumer satisfaction, and halal certificates play a positive role in increasing consumer loyalty, and consumer satisfaction plays a positive role in increasing consumer loyalty. Thus, Bidadari Catering must focus more on optimizing the quality of food provided in addition to the role of halal certificates to increase consumer satisfaction and loyalty.